2013
DOI: 10.1016/j.jagp.2013.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Adherence to Antidepressant Treatment in Later Life

Abstract: Objective Although antidepressants are an effective treatment for later-life depression, older patients often choose not to initiate or to discontinue medication treatment prematurely. While racial differences in depression treatment preferences have been reported, little is known about racial differences in antidepressant medication adherence among older patients. Design Prospective, observational study comparing antidepressant adherence for older African-American and white primary care patients. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 55 publications
(44 reference statements)
3
43
2
1
Order By: Relevance
“…Previous research and our focus group work conducted to inform intervention development suggested that older African Americans prefer nonpharmacological strategies as first-line treatment and also tend to use active coping mechanisms such as engaging in activities to handle daily life stressors. 24,25,26 Further, previous research suggests that depressive symptoms in this group may reflect a confluence of external contextual factors such as poor self-management of chronic disease or financial strain that warrant consideration and modification as part of a depression treatment program.…”
Section: Methodsmentioning
confidence: 93%
“…Previous research and our focus group work conducted to inform intervention development suggested that older African Americans prefer nonpharmacological strategies as first-line treatment and also tend to use active coping mechanisms such as engaging in activities to handle daily life stressors. 24,25,26 Further, previous research suggests that depressive symptoms in this group may reflect a confluence of external contextual factors such as poor self-management of chronic disease or financial strain that warrant consideration and modification as part of a depression treatment program.…”
Section: Methodsmentioning
confidence: 93%
“…The consent form then had to be mailed back by the participant prior to conducting the initial interview. Consistent with prior work by Kales, Nease Jr, Sirey, Zivin, Kim, Kavanagh, Lynn, Chiang, Neighbors, Valenstein, Blow 17 , participants were subsequently excluded if they were found to have cognitive impairment using the Six-Item Screener 18 and/or if their depression was not viewed to be clinically significant (i.e. having a Patient Health Questionnaire [PHQ-9] score of less than 5) 19 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, low educational attainment and female sex have been found to be associated with depression onset (24-26) but not remission (27). Relatedly, female sex has been found to be associated with more severe depressive symptoms (28) and a higher likelihood of receiving treatment for depression (29), while black race is associated with a lower likelihood of initiation and adherence to depression treatment(30). Consequently, whether there are race-related differences in the onset of and recovery from depression in older persons, or whether race is similarly associated with these outcomes in men and women, remains unknown.…”
Section: Objectivementioning
confidence: 99%